2021
DOI: 10.7759/cureus.18121
|View full text |Cite
|
Sign up to set email alerts
|

Acute Psychosis and COVID-19 Infection: Psychiatric Symptoms in Hospitalized Patients

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in various medical and psychosocial consequences globally. Respiratory infections are common among patients infected with the SARS-CoV-2 virus, the causative virus of coronavirus disease 2019 . However, various psychiatric and neurocognitive symptoms and sequelae of COVID-19 have been reported as well.This study aimed to describe two clinical case reports of patients with no prior history of psychiatric illnesses admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“… Limited case details. Kazi et al, 2021 [ 43 ] 49, F, US Admitted to psychiatry with 2 weeks of thoughts of jumping in front of a train, weight loss, agitation, guilt about her grandmother's death 40 years ago and “paranoid delusions.” 3-week history of intermittent cough and anorexia. None None “Tested positive for SARS-CoV-2.” CBC, glucose, BMP, LFTs, TFTs normal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This timeline is particularly important, as evidence stretching back to influenza outbreaks of the 18th and 19th centuries has demonstrated the increased incidence of psychiatric disease following viral infection [ Emily et al, 2020 ]. Only now are we gaining insight into this association, with the pathophysiologic commonality of aberrant inflammation being posited as the mechanism underlying the increased incidence of psychiatric symptoms in those with and recovering from COVID-19 [ Bauer et al, 2019 ; Bryce et al, 2021 ; Emily et al, 2020 ; Jansen et al, 2021 ; Kazi et al, 2021 ; Khademi et al, 2021 ; Mazza et al, 2020 ; Senra H, 2021 ]. COVID-19 has been shown to precipitate neuroinflammation via the release of proinflammatory cytokines both acutely and after the initial infection, with these proinflammatory cytokines having the potential to reduce monoamine levels, blunt neuroplasticity, and promote excitotoxicity [ Bauer et al, 2019 ; Emily et al, 2020 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute infection can also cause delirium and, in some older adults, can be the first sign of infection, even before fever or cough. Unrecognized hypoxia can result in mood dysregulation, confusion, and psychosis ( 3 ) in patients without prior psychiatric history. Anecdotal reports from major hospital systems have found the need for higher than average requirements for both benzodiazepines and opioids related to delirium and agitation in patients requiring mechanical ventilation due to COVID-19 acute respiratory distress syndrome compared with other causes of acute respiratory distress syndrome.…”
mentioning
confidence: 99%